Simplified skin-effect formulation for power transmission lines - Monteiro, Jose Humberto A. [UNESP]; Costa, Eduardo Coelho M.; Pinto, Andre Jinno G. [UNESP]; Kurokawa, Sergio; Gatous, Omar Mohamed O.; Pissolato, Jose (Inst Engineering Technology-iet, 2014)
This study presents a simplified formulation to calculate the skin effect on transmission lines wires. The methodology is developed from the solution of the time-domain Maxwell's wave equations whose frequency-domain solutions are obtained using Fourier transforms. Results obtained from the proposed formulation are compared with those calculated using the conventional method based on the approach by Bessel functions. The proposed skin-effect formulation is also validated based on electromagnetic transients simulations in the time domain considering a conventional 69-kV transmission system.